YOUTH CENTRE AS A ACTIVITIES SPACE TO DEVELOP TALENTS AND INTERESTS OF TEENAGERS IN SUKOHARJO - Ghozali, Raymond Allen; Suparno, Suparno; Samsudi, Samsudi (Universitas Sebelas Maret Surakarta, 2019)
Abstract : Youth Center is a place to contain activities for teenagers in spare time, to distribute the hobby, to developing talents and interests, to find and meet friends, or sometimes just come because they feel bored. Teenagers can learn a variety of ability or even new ability which previously less or not at all under their control. Generally, the activities in the Youth Center activities include sports, arts, and education. In Indonesia, not all regions have satisfy facilities to accommodate the vairety of teenager' activities. Sukoharjo district, an area located in Central Java, bordering with Surakarta City, is one of the various regions in Indonesia are encountered this problem. The lack of facilities intended for teenagers in Sukoharjo, resulting in their less developed on aspects other than academic, because there is little space for them to learn about other things such as sports and the arts are more complex. Youth Center comes with a variety of facilities that can support a variety of positive activities teenagers. Human resourch in Sukoharjo which are given them a place to develop and explore themselves since teenagers and is expected to create a generation of achievers and can make glory for the name of Sukoharjo.